Recruitment And Selection Strategy For Teachers At Al-Kautsar Kindergarten Bandar Lampung - Ayu Anggia, Rifka; Amalia Fitri, Tin; Subandi (Journal of Advanced Islamic Educational Management, 2025)
This study discusses the recruitment and selection strategies of educators as key factors in improving the quality of early childhood education at Al-Kautsar Kindergarten, Bandar Lampung. The background of this research lies in the importance of teacher quality as the main determinant of educational success, the growing demand for qualified educators due to increasing student numbers, and the existing weaknesses in the school’s recruitment strategy. The study aims to describe and analyze the planning, implementation, and evaluation of recruitment and selection strategies for educators. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The results show that planning is based on a needs analysis aligned with the Islamic vision and mission of the school. The recruitment process includes information dissemination, administrative screening, competency tests, microteaching, and in-depth interviews assessing pedagogical skills, personality, and character. Evaluation is conducted by reviewing the selection outcomes and performance of newly hired teachers. The findings conclude that the recruitment and selection strategy at Al-Kautsar Kindergarten is systematic and transparent, yet improvements are still needed in needs mapping and post-placement evaluation. An effective recruitment and selection process is crucial to maintaining teacher professionalism and supporting continuous improvement in the quality of early childhood education.